Functional Outcome of Hybrid Illizarov Technique in patients with Complex Tibial Plateau Fractures - Syed Baqir Jafree, Waqas Siddiqui (Pakistan Journal of Medical & Health Sciences, 2022)
Background:Tibial fractures are the most common long bone fracture, with approximately 25% being open. The majority of open tibial fractures result from a high velocity trauma, such as a motorcycle accident, or a low energy, torsional type injury, such as skiing. They are complex fractures to treat because of the lack of soft tissue coverage and blood supply of the tibial shaft. Aim: To determine the functional outcome of hybridillizarov technique in patients with complex tibial plateau fractures Study Design: Descriptive case series. Place of Study: Orthopedics Surgery Department, Jinnah Hospital, Lahore. Duration of Study: Study was carried out over a period of six months from 28-07-2021 to 28-01-2022 Methods: All the 73 patients fulfilling the selection with complex tibial plateau fractures of Schatzker’s type V and VI were enrolled. Informed consent and demographic information were recorded. All the patients were evaluated for injuries, haemodynamically stabilized. Bone grafting and minimal internal fixation with cc screws was done in severely comminuted fractures. The functional results were measured by Rasmussen’s knee functional score (as per operational definition). Results: Distribution of the functional outcome of the patients was done, it showed that out of 73 patients 20(27.4%) were in excellent outcome, 41(56.2%) were in good outcome, 7(9.6%) were in fair outcome, 5(6.8%) were in poor. Conclusion: Based on our results, the use of hybrid illizarov fixation for the treatment of complex tibial plateau fractures is safe and effective in terms of low rates of complication and good functional results. Keywords: Functional outcome, Tibia plateau fracture, Hybrid ilizarov.